Pain Symptoms in COVID-19 - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objective The clinical manifestations of COVID-19 range from mild symptoms to severe pneumonia and severe organ damage. When evaluated specifically for pain, the data so far have shown that myalgia, headache, and chest pain can be seen in patients at varying rates; myalgia and headache, especially, are among the initial symptoms. Design This retrospective chart review, followed by a descriptive survey design study, was carried out by examining patients afflicted with COVID-19. After discharge, patients were asked about the severity and the body region of their pain, their use of analgesics, their mood and mental health, and their overall quality of life. Results A total of 206 patients with a mean age of 56.24 +/- 16.99 yrs were included in the study. Pain during COVID-19 was found to be higher compared with the preinfectious and postinfectious states. The most frequent painful areas were reported to be the neck and back before the infection, whereas the head and limbs during the infection. The most frequently used analgesic during infection was paracetamol. There was no relationship between the patients' pain and anxiety and depression; the quality of life was found to be worse in patients with persistent pain. Conclusions This study showed that the head and limbs were the most common painful body regions during COVID-19. It was also found that pain can continue in the postinfection period.
Keywords: COVID-19; Headache; Infection; Pain